Implementation of 5G Telecommunication Network Services in Indonesia based on Techno-economic Analysis - Siti Hajar Komariah; Rd. Rohmat Saedudin; Rizki Yantami Arumsari; Umar Yunan KSP Yunan KSP (Society of Visual Informatics, 2023)
The 2300 MHz spectrum is a medium band that telco operators will not pay much attention to when they deploy 5G. They are more comfortable at 2.6 GHz, 3.5 GHz, 26 GHz, and 28 GHz, in addition to 700 MHz for the breadth of coverage. The performance of cellular telecommunications services based on 5G technology is possible for new operators, although it will be carried out as stand-alone services. This opportunity will be taken by looking at internet subscriber data/data communication from existing operators as active internet users, which is quite large and has a potential of over 250 million users. There has been no previous study regarding the feasibility of deploying this 5G technology-based Broadband Wireless Access (BWA) Network. Based on the experience of implementing previous generations of telecommunication service technology, the government and operators need to be careful in determining the right moment to deploy this 5G technology service, which is predicted to be able to provide broadband services with streaming capabilities of 10 to 100 times the streaming speed of 4G technology. It should be noted that the lack of success of 3G performances in 2006 from 2G, 2.5G, and 2.75 G. Almost all operators who were expected to be very lucky turned out to be not optimal; even now, only 4 operators are playing on 3G. where they have not been able to force users of the 2G generation to switch to 3G, including in big cities where the performance of the 3G network is not yet optimal and evenly distributed. Still, many areas are blank spots from 3G networks and services. From this experience, scientific studies are needed to ensure the feasibility of the upcoming 5G BWA business and identify business opportunities that can be implemented. The feasibility analysis must be viewed from various aspects, namely aspects of technical readiness, market aspects, and financial aspects in terms of the techno-economics of the operators who will provide 5G telecommunications services by calculating several essential parameters as a measure of business feasibility, namely Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP).